Prestação de contas no terceiro setor: a dicotomia do marco regulatório - Tozzi, José Alberto (2010)
This study aims to examine the accountability of the Third Sector to brazilian regulation in the face of the current regulatory framework by seeking to discern whether the current regulation is sufficient to ensure provision of effective and transparent accounts that will serve not only for the purpose of tax relief, but also to increase the credibility and efficiency of the sector. Currently there is a dichotomy: entities do certify and will be subject to a large volume of accountability or they do not certify and create a legal uncertainty existence. For this, the methodology was made from an exploratory descriptive, qualitative approach, having been used as primary documents, such as viewing the non-profit and database of regulatory bodies such as the literature review, basement of the content. Thus, we sought to include the analysis of the regulatory framework based on the understanding of certification and control over the entities in Brazil, determining the need and obligation to supply all, and the mapping of interest entities that joined the social legislation and certification currently operation. In addition, we applied a semi-structured questionnaire with the participants of an event on accountability promoted by the Law Commission of the Third Sector OAB-SP, this questionnaire consists of ten standardized open questions, the answers take shape from the opinions of the interviewee , and subsequently analyzed and quantified, giving part of the search results. The study concludes that adherence to the regulatory framework in Brazil is still very small, because even after the new legislation (Law OSCIP and New Law of Philanthropy), there is no requirement for the non-profit organizations in order to be truly recognized and legalized, have a conditional certification of the accounts more accurate, clear and public scrutiny, a factor that has prevented the effective emergence of a culture of accountability in the Third Sector in Brazil